Massive occurrence of Podagrica fuscicornis (L.) (Coleoptera, Chrysomelidae) on common marshmallow (Althaea officinalis L.) - Tanja BOHINC; Matej VIDRIH; Stanislav TRDAN (Acta Agriculturae Slovenica)
In May 2011 we noticed high number of Podagrica fuscicornis adults on the leaves of common marshmallow (Althaea officinalis) grown on Laboratory Field of Biotechnical Faculty in Ljubljana. In Slovenia, this beetle was already recorded earlier but it did not caused any damage on common marshmallow (Althaea officinalis). Due to the feeding of beetles on leaves, 1 to 2 mm large holes appear. By expecting climate changes, already known bionomics of some related species and giving more emphasis on herb production in the future, Chrysomelid P. fuscicornis might represent medium sized biological factor in producing common marshmallow.